Burden of HPV-induced diseases and cost effectiveness of catch-up vaccination in Czech Republic: a model-based study - Vojtech Kamenský; Lukáš Dostálek; Martin Rožánek; Aleš Tichopád; Roman Prymula; Ivana Šarkanová (BMC Public Health)
Abstract Objectives Human papillomavirus (HPV) infections are highly prevalent sexually transmitted infections, notably associated with various cancers. This study analyses the health and economic impacts of HPV-associated diseases in the Czech Republic and evaluates the cost-effectiveness of a catch-up vaccination program. Methods Utilizing a Markov multistate model, the study assesses the lifetime impacts and costs related to HPV infections. Cohorts of ages 15–21 were simulated to assess the impact of catch-up vaccination outside the 11-year-old age group. Results The total quality-adjusted life years (QALYs) for the female and male cohorts (together 119,362 individuals) were higher in the vaccination scenario compared to the non-vaccination scenario. The increase in QALYs was 122,246 and 200,852 respectively, when considering the actual vaccination rates. Across both cohorts, 329 cancer-related deaths were prevented. In the probabilistic sensitivity analysis for the female population, vaccination was the dominant strategy in 99.3% of iterations. In the male population, vaccination was the dominant strategy in 80.3% of iterations. The implementation of catch-up vaccination for the 15–21 age group significantly increased QALY gains and reduced life-years-lost (LYLs). In the female cohort, all analysed rates of catch-up vaccination were the dominant strategy, while in the male cohort, the incremental cost-effectiveness ratios (ICERs) remained consistently below 42,000 CZK/QALY. Conclusions The catch-up vaccination program for 15-21-year-olds is cost-effective and can prevent a significant number of HPV-related cancers in both men and women.